EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) SEBAGAI PEWARNAAN ALTERNATIF ALAMI PREPARAT SECTION TANAMAN CABE MERAH BESAR (Capsicum annuum L.) - Chasan Bisri; Yuni Pantiwati; Sri Wahyuni (Universitas Sebelas Maret, 2014)
Abstract - Plants section slides are a method of making mikroteknik slides intended for objects that are big and bold on the plant, so that the tissue can be seen under a microscope. Observations on the tissue of plants section slides big red chili (Capsicum annuum L.) will be more easily if use a dye to staining the tissue. The aim of this staining is to clarify the various tissues of plants, so that it can be distinguished and being reviewed with a microscope. Exploration of exploiting alternative coloring matter of being cheaper and has a high affinity towards cell components is very important, so the use of extracts of rosella petals flower (Hibiscus sabdariffa L.) as alternative natural dyes are expected to produce natural staining alternative to replace staining is usually used. The aims of this research to know the effect of granting the concentration extract of rosella petals flower (Hibiscus sabdariffa L.) as a natural dye to the quality of plants section slides Capsicum annuum L. and to know and compare quality of the picture of the plants section slides Capsicum annuum L. results of extract of rosella petals flower (Hibiscus sabdariffa L.) natural staining with results of safranin synthetic staining.The type of this research is experimental research. This research was conducted in the Laboratory of Biology of University of Muhammadiyah Malang which took place on March 11-March 15, 2014. This research used the concentration of extract of rosella petals flower is 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% with 3 times repeats. Data collected by direct observation and documentation directly from the camera by using a microscope. Data were analyzed with descriptive qualitative analyses and descriptive quantitative from observations results and documentation of the results directly from the microscope. The results showed there is the staining effect of various concentrations of the extract of rosella petals flower to the quality of plants section slides Capsicum annuum L. Quality of plants section slides Capsicum annuum L. results of natural staining from extract of rosella petals flower has a good quality picture of slides. Comparison of the quality of the plants section slides Capsicum annuum L. results of extract of rosella natural staining petals flower did not vary much with results safranin synthetic staining. Keywords: Extract, Hibiscus sabdariffa L., Natural staining, Section slides, Capsicum annuum L.